Crosstalk between autophagy and metabolic regulation of (CAR) T cells: therapeutic implications - Panahi Meymandi, Ahmad Reza; Akbari, Behnia; Soltantoyeh, Tahereh; Hadjati, Jamshid; Klionsky, Daniel J.; Badie, Behnam; Mirzaei, Hamid Reza (Frontiers in Immunology, 2023)
Despite chimeric antigen receptor (CAR) T cell therapy's extraordinary success in subsets of B-cell lymphoma and leukemia, various barriers restrict its application in solid tumors. This has prompted investigating new approaches for producing CAR T cells with superior therapeutic potential. Emerging insights into the barriers to CAR T cell clinical success indicate that autophagy shapes the immune response via reprogramming cellular metabolism and vice versa. Autophagy, a self-cannibalization process that includes destroying and recycling intracellular components in the lysosome, influences T cell biology, including development, survival, memory formation, and cellular metabolism. In this review, we will emphasize the critical role of autophagy in regulating and rewiring metabolic circuits in CAR T cells, as well as how the metabolic status of CAR T cells and the tumor microenvironment (TME) alter autophagy regulation in CAR T cells to restore functional competence in CAR Ts traversing solid TMEs.